Interaction of a Potential Anticancer Agent Hypericin and its Model Compound Emodin with DNA and Bovine Serum Albumin - Staničová, Jana; Verebová, Valéria; Beneš, Jiří (In vivo (Athens, Greece), 2018)
BACKGROUND/AIM: We report the incorporation of prospective anticancer agent hypericin into DNA and bovine serum albumin (BSA), respectively, with emphasis on comparison of the differences in interaction mode between hypericin and its model compound emodin. MATERIALS AND METHODS: Spectrophotometric methods were used for determination of the binding constants of the drug complex with biomacromolecules. Differential scanning calorimetry was applied for evaluation of drug-macromolecule complex thermal stability. RESULTS: The strength of interaction expressed by binding constants was found to be 4.0×104 l/mol for hypericin-DNA and 8.1×104 l/mol for emodin-DNA complex. Both molecules stabilize bovine serum albumin macromolecule and bind into the hydrophobic cavity in IIA subunit but their localization within the molecule is different. CONCLUSION: Anticancer agent hypericin and its derivative emodin interact with DNA with medium strength and are probably incorporated into the groove of DNA by hydrogen bonds. Bovine serum albumin can serve as a transport protein for hypericin since the binding force between both molecules is adequate.
Keywords: Animals; Anthracenes; Emodin; vazba proteinů; Molecular Structure; Structure-Activity Relationship; DNA; Perylene; sérový albumin hovězí; Antineoplastic Agents; Serum Albumin, Bovine; protinádorové látky; Hypericin; perylen; anthraceny; molekulární struktura; spektrální analýza; interaction; serum albumins; Thermodynamics; vztahy mezi strukturou a aktivitou; zvířata; termodynamika; Protein Binding; emodin; Spectrum Analysis; thermal stability